Appointment of arbitrators in cases of indeterminate seat (decision of the High Court of Justice of Madrid of 8 May 2018) - Gómez Jene, Miguel (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
Commentary on the resolution of the High Court of Madrid declaring its territorial jurisdiction to appoint an arbitrator in a case in which the seat of the arbitration was not determined and neither the parties had its residence in Spain.